Structure behavior of concrete filled double-steel-plate composite walls under fire. Issue 8 (June 2019) - Wei, Fangfang; Zheng, Zejun; Yu, Jun; Wang, Yongquan
Concrete filled double-steel-plate composite walls with shear studs, one type of steel–concrete–steel walls, are recently developed and have been used in high-rise buildings, for which fire safety is a big concern. In order to investigate the fire endurance of this new type of concrete filled double-steel-plate composite walls, three specimens with different axial compression ratios and different lengths and intervals of shear studs were tested under one-side ISO-834 standard fire to obtain the temperature distribution, deformation, and detailed failure modes. Each specimen consisted of a concrete filled double-steel-plate composite wall-body and two boundary columns. Moreover, finite-element-based numerical investigations were conducted to confirm and extend experimental findings. All the concrete filled double-steel-plate composite walls failed in compression–flexure mode with the local buckling at the compressive steel plate. The results indicate that the fire endurance of concrete filled double-steel-plate composite walls is significantly affected by the axial compression ratio, the eccentricity of the axial load, and the bond strength between shear studs and concrete. Axial compression ratio, defined as the ratio of axial compression to the nominal compressive capacity of concrete filled double-steel-plate composite walls, has both positive and negative effects on the fire endurance of concrete filled double-steel-plate composite walls. The axial load eccentricity toward the unexposed side is much more detrimental to the fire endurance of concrete filled double-steel-plate composite walls than the one toward the exposed side. In engineering practice, it is recommended that proper intervals (not greater than 300 mm) and lengths (not less than 40 mm) of the shear studs should be used to ensure the bond between concrete and steel plates.